Effects of ultrasound irradiation on enzymatic hydrolysis of protein and application for the determination of tetracyclines in complex matrices. Issue 10 (11th May 2017) - Zhou, Qian; Wang, Hong; Zhu, Kuanzheng; Zhu, Lihua; Zhou, Shengyin; Peng, Jin; Lu, Xiya
Abstract : The widespread use of tetracyclines (TCs) in food animals has led to concerns regarding unsafe residue levels in feed, food and manure. The determination of TCs in such matrices suffers from interference by the interactions between proteins and TCs. Three deproteination methods were compared in this study. In contrast with acid deproteination, which caused a large loss of TCs due to the strong adsorption of TCs on protein precipitates, a normal enzymatic hydrolysis was confirmed to have a merit of effectively releasing TCs from protein matrices, but required treatment time as long as 16 h. The adoption of ultrasound irradiation was proposed to shorten the enzymatic hydrolysis time. After investigating the effects of ultrasound power and irradiation time, the conditions of the ultrasound‐enhanced enzymatic hydrolysis were optimized as ultrasound power of 100 W and irradiation time of 6 min. The ultrasound‐enhanced enzymatic hydrolysis treatment of 6 min yielded recovery of TCs (from protein‐containing matrices) as high as that obtained by the normal enzymatic hydrolysis treatment of 16 h. The acceleration effect of ultrasound irradiation was attributed to ultrasound‐induced cavitation, which increased exposure of both the functional groups of trypsin and the C‐terminal amino acid in the protein that was a cleavage site for trypsin attack. When the ultrasound‐enhanced enzymatic hydrolysis method was used to determine TCs in complex matrices, it was found that this new method achieved recoveries of 89.5, 117.7, 110.4 and 100.0% for oxytetracycline, tetracycline, chlortetracycline and doxycycline, being much higher than those (29.6–39.4%) obtained using the common acid deproteination process. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : The interactions between tetracyclines and protein aggregates are clarified. Effect of various parameters was studied on ultrasound‐enhanced enzymatic hydrolysis. Ultrasound changed the secondary structure of trypsin and improved its activity.